A Six Year Prospective Study of Fibrinogen and Other Risk Factors Associated with Mortality in Stable Claudicants - Banerjee, A K; Pearson, J; Gilliland, E L; Goss, D; Lewis, J D; Stirling, Y; Meade, T W (Thrombosis and Haemostasis, 1992)
A total of 333 patients with stable intermittent claudication at recruitment were followed up for 6 years to determine risk factors associated with subsequent mortality. Cardiovascular diseases were the underlying cause of death in 78% of the 114 patients who died. The strongest independent predictor of death during the follow-up period was the plasma fibrinogen level, an increase of 1 g/l being associated with a nearly two-fold increase in the probability of death within the next 6 years. Age, low ankle/brachial pressure index and a past history of myocardial infarction also increased the probability of death during the study period. The plasma fibrinogen level is a valuable index of those patients with stable intermittent claudication at high risk of early mortality. The results also provide further evidence for the involvement of fibrinogen in the pathogenesis of arterial disease.